2023
DOI: 10.1038/s41598-023-31681-x
|View full text |Cite
|
Sign up to set email alerts
|

Ecological risk assessment of trace elements (TEs) pollution and human health risk exposure in agricultural soils used for saffron cultivation

Abstract: Contamination of farmland soils by trace elements (TEs) has become an international issue concerning food safety and human health risks. In the present research, the concentrations of TEs including cadmium (Cd), cobalt (Co), chromium (Cr), copper (Cu), manganese (Mn), nickel (Ni), lead (Pb), zinc (Zn) and iron (Fe) in soils of 16 farmlands were determined in Gonabad, Iran. In addition, the human health risks due to exposure to the TEs from the soils were assessed. Moreover, the soil contamination likelihood wa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 87 publications
1
25
0
Order By: Relevance
“…The concentrations of Cu in the soil with the application of IF and PM exceeded the Canadian standard. The trend in heavy metal concentrations in the soils across all treatments was Fe > Zn > Cu > Pb > Cr > Cd, which is consistent with other studies reported in the literature [10] , [67] , [84] . The presence of heavy metals (Cu, As, Zn, Cd) in animal manure could be related to the diet of the animals, due to the excessive application of additives to animal's feed to improve growth, increase weight, food efficiency, reproduction of the animals [44] , [45] .…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The concentrations of Cu in the soil with the application of IF and PM exceeded the Canadian standard. The trend in heavy metal concentrations in the soils across all treatments was Fe > Zn > Cu > Pb > Cr > Cd, which is consistent with other studies reported in the literature [10] , [67] , [84] . The presence of heavy metals (Cu, As, Zn, Cd) in animal manure could be related to the diet of the animals, due to the excessive application of additives to animal's feed to improve growth, increase weight, food efficiency, reproduction of the animals [44] , [45] .…”
Section: Resultssupporting
confidence: 91%
“…The use of poultry and cattle manure, inorganic fertilizers, and pesticides in cultivation contributes to the release of heavy metals, thus contaminating the soil [84] . However, for the conditions of our experiment, it was not demonstrated that there is a health risk for consumers due to exposure to heavy metals.…”
Section: Resultsmentioning
confidence: 99%
“…Heavy metals in soil could enter agricultural products and pose both carcinogenic and non-carcinogenic health risks for human beings, and children are especially vulnerable [ [1] , [2] , [3] , [4] , [5] ]. The main types of heavy metal or metalloid in soil include Cd, Hg, As, Pb, Cr, Cu, Zn, Ni, etc .…”
Section: Introductionmentioning
confidence: 99%
“…The reactions of plants that are grown or occur naturally in contaminated areas also reveal characteristic signs of the toxic effects of these PTEs. Moreover, the danger connected with the presence of PTEs in the soil is connected with the possibility of them spreading to surface and ground waters and their contamination 3 .…”
Section: Introductionmentioning
confidence: 99%